Österreich im KSZE-Prozess 1969-1983. Neutraler Vermittler in humanitärer Mission - Gilde, Benjamin (Quellen und Darstellungen zur Zeitgeschichte, 2013)
Austria was active in the CSCE (Conference on Security and Cooperation in Europe) negotiations, primarily in the contentious areas of humanitarian issues and human rights. Despite consistent claims of neutrality, Vienna supported the Western position on all important questions. Benjamin Gilde's broadly researched study offers major insight into the history of the humanitarian aspect of the CSCE.